Riding to the top - A systematic review on multidimensional performance indicators in surfing - Klingner, F. C.; Klingner, F. P.; Elferink-Gemser, M. T. (International Journal of Sports Science & Coaching, 2022)
Identifying high-performing and promising athletes is an important task of national surf associations. However, the scientific foundation of performance indicators in surfing has only developed in recent years. This review aimed to (1) find out which performance characteristics discriminate between surfers of different skill levels, and (2) point out gaps in the existing literature and direct future studies by applying the Groningen Sport Talent Model (GSTM) to categorize findings. A systematic review of PubMed, Web of Science, MEDLINE and PsycInfo databases was performed according to the PRISMA guidelines. A total of thirty-one studies were included. Studies were found on anthropometric, physiological, technical, and tactical, but not on psychological characteristics of surfing performance. In total only six studies included female surfers. Findings suggest that a few performance indicators exist in relation to associations between physical capacities and surfing skill. For one, relative arm span seems to be beneficial to surfing performance and discriminates between differently skilled surfers. Additionally, 15 m and 400 m in-water paddle performance, as well as relative upper and lower-body strength also tend to be better in superior surfers. Technical skills, such as the ability to perform aerials and tube rides with a high completion rate, translate directly into an enhanced scoring potential and therefore success in surfing competitions. While a variety of characteristics for high-performance surfing are already indicated, future research needs to focus on developing reliable methods with higher ecological validity to assess these skills. Apart from the in-water paddle tests, most indicators lack a broadly accepted testing method. Especially, the field of psychological skills in surfing should be addressed more in the future.